2(9n-6)=

Simple and best practice solution for 2(9n-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(9n-6)= equation:


Simplifying
2(9n + -6) = 0

Reorder the terms:
2(-6 + 9n) = 0
(-6 * 2 + 9n * 2) = 0
(-12 + 18n) = 0

Solving
-12 + 18n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 18n = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 18n = 0 + 12
18n = 0 + 12

Combine like terms: 0 + 12 = 12
18n = 12

Divide each side by '18'.
n = 0.6666666667

Simplifying
n = 0.6666666667

See similar equations:

| F=77 | | 3x(2x^2+7)= | | 8(-4+r)=-112 | | 0.34*-70.6= | | 0=-16t^2+40t+12 | | 8x+2=3*x | | 1+6-(5+1)= | | a(4+3)= | | 7x-10=40x+1 | | 6x^4+5x^2-4=0 | | 7x-10=40x+q | | (a+12)(a^2-7a+7)= | | (N+3)(n+6)=0 | | ax-bx=12 | | cx+3h=58 | | 0=16-4x^2 | | b+4=12 | | 2m^2=-8-8m | | 6y^2-13y+6=0 | | .75x+3=9 | | -12(x-4)=-3(6x+2) | | -x-3=-4x-14 | | 0.65x+.05(8-x)=.10(-8) | | 3lx-5l-2x=10 | | x-1(3x-9)=-5 | | 4y=9x+4f | | a-5=2a | | x-1(3x-9)=5x | | 4x^2-32x=-60 | | a+1-5*6=b+56 | | -3(x-1)=2(1-2x) | | -8(1+5r)=11(-4r-3)-11 |

Equations solver categories